CORRELATION OF C-REACTIVE PROTEIN LEVELS WITH CLINICAL OUTCOME INTRACEREBRAL HEMORRHAGE STROKE PATIENTS - Setianto, Catur Ari; Purnomo, Hari; Marhaendraputro, Eko Arisetijono; Santoso, Widodo Mardi (Malang Neurology Journal, 2015)
Background. Increased levels of markers of inflammatory factors after hemorrhage stroke was able to predict poor clinical outcome. Until now, the role of C Reactive Protein (CRP) in the local inflammatory response and clinical determinants output remains unclear.Objective. To investigate the correlation of CRP level with poor clinical outcome as measured by Barthel Index. Methods. This study was an observasional cohort porspective study performed on haemorrhage stroke patients in Saiful Anwar General Hospital in Februari 2014 until April 2014.Results. There was significant correlation (p=0,01, r=0,613) between CRP levels to poor clinical outcome measured by Barthel Index.Conclusion. C Reactive Protein levels could predict poor clinical outcome as measured by Barthel Index in intracerebral hemorrhage patients.